Expanding the strike zone : baseball in the age of free agency - Gilbert, Daniel A. (University of Massachusetts Press, 2013)
With its iconic stars and gleaming ballparks, baseball has been one of the most captivating forms of modern popular culture. This book examines the history and meaning of the sport's tumultuous changes since the mid-twentieth century, amid Major League Baseball's growing global influence. From the rise of ballplayer unionism to the emergence of new forms of scouting, broadcasting, and stadium development, the author shows that the baseball world has been home to struggles over work and territory that resonate far beyond the playing field. -- Publisher's description.